Alternative Organic Substrates in the Germination and Initial Growth of Corn (Zea mays L.) Seedlings Under Nursery Conditions - Cardoza-Viera, Andrea; Arévalo-Valladolid, Diego; Javier-Alva, Javier; Peña-Castillo, Ricardo; Chanduví-García, Roger; Quiroz-Calderón, Marcos; Álvarez-Bernaola, Luis; Galecio-Julca, Miguel; Calero-Merino, Mariano; Morales-Pizarro, Davies Arturo (REVISTA TERRA LATINOAMERICANA, 2024)
Maize is a grass of great socio-economic commercial interest. In Peru, it is sown directly in the field, with irregular germination and seedling mortality. Our aim was to evaluate the combination of alternative organic substrates in the germination and initial growth of maize seedlings under nursery conditions. Four treatments were established consisting of the combination of sand (S), rice husk (RH) and humus (H): T1 (100% S-Test), T2 (75% S+25% RH), T3 (50% S+25% RH+25% H) and T4 (50% RH+50% H). The following parameters were evaluated: Electrical conductivity (EC), substrate pH, emergency percentage (EP), mean time emergence (MTE), plant height (PH), root length (RL), stem diameter (SD), number of leaves (NL), leaf area (LA), biomass weight (BW): fresh biomass (FB), dry biomass (DB), fresh root (FR) and dry root (DR). The data obtained was subjected to Analysis of Variance (ANOVA) and correlation. T4 showed the best values in the study. The MTE exhibited a (-) correlation with DR and FB. RL showed a (+) correlation with SD. FR exhibited a (+) correlation with DR, LA, NL, and FB. DR showed a (+) correlation with FB and NL. DB exhibited a (+) correlation with PH. PH showed a (+) correlation with SD, LA, NL, and FR. SD exhibited a (+) correlation with LA, NL, and FB. LA showed a (+) correlation with NL and FB. NL exhibited a (+) correlation with FB. The organic substrates improved the variables evaluated in corn.